Implementation of The Pancasila Student Project and Work Culture Towards The Performance of Teachers of SMK Centers of Excellence In West Kalimantan - Revi Sesario (Journal Research of Social Science, Economics, and Management, 2023)
The project to strengthen Pancasila students is a program of the Ministry of Education of the Republic of Indonesia in Vocational High Schools (SMK) which will be implemented in 2021-2022. The program's achievement indicator is the improvement of students' ability to adapt to the challenges and global dynamics of the business and industrial world. The specific objective is to create graduates who continue to the highest level of education, are able to work and have entrepreneurial skills. The dimensions that became the research variables for Pancasila students included: 1) Faith and piety to God Almighty and noble character; 2) Independent; 3) Cooperate; 4) Global Development; 5) Critical Reasoning and 6) Creative is further linked to competence through the concept of work culture, including: 1) Relations between colleagues and students; 2) Commitment and 3) Discipline to measure teacher performance includes: 1) Improvement of Soft Skills and Hard Skills. The method used was multiple linear regression with a total sample of 60 productive teachers majoring in agriculture and plantations for the observation period July-December 2021 and August-December 2022. The results showed that the profile dimensions of Pancasila students and the Work Culture Climate created at Vocational High Schools would have a significant effect on improving Performance of Productive Teachers at the West Kalimantan Agriculture and Plantation Service. It is necessary to increase the dimensions of independence and critical reasoning skills for students with competence in agriculture and plantations that are licensed nationally based on industry.